Outcome of Refractory Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The records of twenty-two children, ages 4.5 months to 18 years, treated for refractory status epilepticus (RSE) between 1992 and 2000, were reviewed retrospectively at Children's Hospital, Boston.